Pruritus in hemodialysis patients: Results from Fresenius dyalisis center, Banja Luka, Bosnia and Herzegovina - Zoran Vrucinic; Biljana Jakovljevic; Ljubisa Preradovic (Our Dermatology Online, 2015)
Introduction: Uremic pruritus (UP) is a common and distressing complication of end-stage renal disease (ESRD). Aglobal cross-sectional study of 18,000 hemodialysis patientsreported a 42% prevalence of moderate or extreme UP, which was strongly associated with sleep disturbance, depression, impaired quality of life, and mortality. Pruritus is commonly encountered in individuals with end-stage renal disease (ESRD) on hemodialysis (HD). Materials and Methods: This cross-sectional study was performed in order to find out the prevalence of pruritus in patients on regular maintenance hemodialysis (HD) as well as to analyze its relationship to age, sex of the patient, duration of hemodialysis in months per patient, serum levels of phosphate, PTH, KT/V (index of dialysis dose), parameters in the beggining of the study and six months after. The data were analyzed by descriptive statistics- Wilcoxon Signed Rank Test and Chi-square test with Yates correction factor. Results: Sixty and two patients with ESRD (age ranging from 31 to 87years) free from systemic, skin or psychiatric disorders and other secondary causes attributable to pruritis, undergoing maintenance HD (duration on HD 4-348months; mean 86.97 and median 79,5months) at Fresenius dialysis center, Banja Luka, Bosnia and Herzegovina were evaluated for pruritus. Pruritus has been discovered in 21 out of 34males (54,8%) and 6 out of 28females (22,2%). Our study as many others showed that pruritus is very common (45.2%) in HD patients. Applying c2 test with Yates correction factor is highly statistically significant (c2 = 8.003, p = 0.005) by gender. Research of the gender revealed that pruritus appeared more in men analysis. There were no significant differences between other measured markers: to age, duration of hemodialysis in months per patient, serum levels of phosphate, PTH, KT/V (index of dialysis dose) in patients with pruritus and in patients without pruritus. Conclusions:This first cross-sectional study describes key features UP in Republic of Srpska (Bosnia and Herzegovina) and results that the UP is significantly more common in men. This study demonstrates that the serum level of PTH and phosphate isn't associated with the incidence of pruritus in HD patients.